1997
DOI: 10.1002/jlac.199719970703
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the [1,2]‐Wittig Rearrangement

Abstract: The stereochemical features and synthetic potentials of the [1,2]‐Wittig rearrangement are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 39 publications
5
94
0
Order By: Relevance
“…The isomerizations of ethers under basic conditions to the corresponding alcohols are known as Wittig rearrangements and can proceed via two main pathways: A stepwise [1,2]-migration involving a radical/radical-anion species 1 or via a concerted symmetry-allowed [2,3]-shift. 2 In addition, during the reorganization of allylic ethers [1,4]-Wittig rearrangements can compete with the [1,2]-migration and give rise to carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The isomerizations of ethers under basic conditions to the corresponding alcohols are known as Wittig rearrangements and can proceed via two main pathways: A stepwise [1,2]-migration involving a radical/radical-anion species 1 or via a concerted symmetry-allowed [2,3]-shift. 2 In addition, during the reorganization of allylic ethers [1,4]-Wittig rearrangements can compete with the [1,2]-migration and give rise to carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…1 In cases of limited radical stability of the migrating group, carbanion-stabilizing groups similarly facilitate [1,2]-migrations. 1 In contrast, the yield of [1,4]-Wittig products has been reported to be relatively insensitive to substitution at the α- or γ-position of the allylic moiety, 3 although Schlosser observed that [1,4]-/[1,2]-selectivity is diminished with increasing alkyl substitution about the migrating carbon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that the Wittig rearrangement is a synthetically useful tool in organic chemistry for the construction of secondary alcohols, the synthetic utilization of the [1,2]‐Wittig rearrangement remains severely limited because of rather low yields and the restricted range of substrates in most cases . Inspired by previous examples of the diastereoselective [1,2]‐Wittig rearrangement, we have successfully developed a facile and practical methodology for the stereoselective construction of the secondary alcohol moiety as well as the highly efficient synthesis of enantiomerically pure BINOL‐derived diols, the aforementioned Ar‐BINMOLs, with axial and sp 3 central chirality through the [1,2]‐Wittig‐rearrangement‐based axial‐to‐central chirality transfer or diastereoselective induction . In this diastereoselective Wittig rearrangement (Scheme ), the stereoselective process exhibited a perfect level of diastereoselectivity, good substrate scope, and excellent yields, thus allowing access to a broad range of chiral Ar‐BINMOLs.…”
Section: The Stereoselective Synthesis Of Ar‐binmols With Axial and Smentioning
confidence: 99%
“…This happens frequently when highly enolized aldehydes or ketones (e.g. [1,2]-Wittig (X = O) [190][191][192], Stevens (X = NR 2 + ) [193][194][195], or related rearrangements [195,196]) or a-elimination to yield carbenes (Scheme 5.20). In these circumstances transmetalation (e.g.…”
Section: A-heteroatom Carbanionsmentioning
confidence: 99%